2009
DOI: 10.5194/acp-9-189-2009
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of aerosol absorption and scattering in the Mexico City Metropolitan Area during the MILAGRO field campaign: a comparison of results from the T0 and T1 sites

Abstract: Abstract. In March 2006, a multiagency field campaign was undertaken in Mexico City called the Megacities Initiative: Local and Global Research Observations (MILAGRO). Two of the five field components of the MILAGRO study focused a major part of their efforts on atmospheric particulate emissions from the Mexico City basin and their effects on radiative balance as a function of time, location and processing conditions. As part of these two MILAGRO components, measurements of aerosol optical properties were obta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
46
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 97 publications
(115 reference statements)
10
46
0
Order By: Relevance
“…Substantial vertical layering of the aerosol and regional differences in the Valley of Mexico for aerosol scattering and extinction was also found. Enhanced UV absorption (300-450 nm) of incoming solar radiation was found to be substantial and was likely due to both SOA formation as well as from biomass burning sources (Corr et al, 2009;Marley et al, 2009b), consistent with a previous study during MCMA-2003. The wavelength dependence of absorption measured at 470, 530 and 660 nm on the C-130 was higher with higher organic fraction of non-refractory mass of submicrometer particles, and this relationship was more pronounced under high single scattering albedo, as expected for the interplay between soot and colored weak absorbers (some organic species and dust) .…”
Section: Aerosol Optical Properties and Radiative Influencessupporting
confidence: 77%
See 2 more Smart Citations
“…Substantial vertical layering of the aerosol and regional differences in the Valley of Mexico for aerosol scattering and extinction was also found. Enhanced UV absorption (300-450 nm) of incoming solar radiation was found to be substantial and was likely due to both SOA formation as well as from biomass burning sources (Corr et al, 2009;Marley et al, 2009b), consistent with a previous study during MCMA-2003. The wavelength dependence of absorption measured at 470, 530 and 660 nm on the C-130 was higher with higher organic fraction of non-refractory mass of submicrometer particles, and this relationship was more pronounced under high single scattering albedo, as expected for the interplay between soot and colored weak absorbers (some organic species and dust) .…”
Section: Aerosol Optical Properties and Radiative Influencessupporting
confidence: 77%
“…Thus other urban and regional sources of modern carbon are important in Central Mexico, such as biogenic SOA , food cooking (Mugica et al, 2009), and other anthropogenic open burning activities (e.g., trash burning and biofuel use (Christian et al, 2010)). Larger relative amounts of biomass burning aerosols were noted at the T1 regional site than the urban T0 site Marley et al, 2009b), consistent with the megacity having a significant fossil fuel input, but both sites were heavily impacted by recent carbon sourced carbonaceous aerosols from local and regional burning and also other modern carbon-containing sources as discussed above.…”
Section: Aerosol Optical Properties and Radiative Influencesmentioning
confidence: 63%
See 1 more Smart Citation
“…The scattering coefficient, B sct , is extremely well correlated with the POM for all air flow directions. Marley et al (2009) Marley el al. (2009).…”
Section: Particle Optical Propertiesmentioning
confidence: 99%
“…Marley et al (2009) measured the aerosol absorption and scattering in the MCMA during MILAGRO; they reported that the single scattering albedo (SSA) at 550 nm for the fine mode aerosols ranged from 0.47 to 0.92 at the T0 supersite (located in the northern part of Mexico City), suggesting that Mexico City environment has high levels of fine mode absorbing aerosols. Using direct measurements of the optical and microphysical characteristics of atmospheric soot particles, Moffet and Prather (2009) found that, within 3 h after sunrise, photochemical activity leads to the rapid conversion of fresh non-spherical soot to aged spherical coated soot particles, which become the dominant contributor to aerosol absorption during mid-day.…”
Section: Introductionmentioning
confidence: 99%